Requeriments elicitaction of resilience for systems information based on the model CERT-RMM [Elicitación de requisitos de resiliencia para sistemas de información basado en el modelo CERT-RMM] - Palacios A., J. (2014)
It intends emphasize the important of an effective requirements elicitation of resilience to determine the resilience of systems information based on elicitation techniques and the CERT-RMM model, furthermore of a comparison between the types of requirements, elicitation technical, software resiliency features and areas of CERT-RMM model stipulating the relationship between resilience activities and requirements elicitation